2002
DOI: 10.1080/10915810290096306
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Carcinogenic Potential of Insulin Glargine (LANTUS) in Rats and Mice

Abstract: Insulin glargine (LANTUS) is a new, long-acting insulin analogue with a stable profile of action. The purpose of these studies was to evaluate the carcinogenic potential of insulin glargine in rats and mice. General toxicity studies were conducted in NMRI mice (3 months' duration) and rats (Wistar rats in the 3- and 6-month studies and Sprague-Dawley rats in the 12-month study) to determine the optimal dose of insulin glargine for long-term carcinogenicity studies. Based on these results, groups of Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 21 publications
2
76
1
2
Order By: Relevance
“…The daily doses tested were 12.5, 50 and 200 U/kg, and malignant tumours developed in 0, 11% and 23% of the rats, respectively. Insulin glargine, by contrast, was tested at the lower daily doses of 2, 5 and 12.5 U/kg [39], the last of which is said to correspond to human daily doses of approximately 100 U (rats) or 50 U (mice). It is worthy of note that insulin B10Asp would have passed the carcinogenicity testing to which insulin glargine was subjected and would now be in clinical use.…”
Section: Carcinogenicity Studies In Rodentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The daily doses tested were 12.5, 50 and 200 U/kg, and malignant tumours developed in 0, 11% and 23% of the rats, respectively. Insulin glargine, by contrast, was tested at the lower daily doses of 2, 5 and 12.5 U/kg [39], the last of which is said to correspond to human daily doses of approximately 100 U (rats) or 50 U (mice). It is worthy of note that insulin B10Asp would have passed the carcinogenicity testing to which insulin glargine was subjected and would now be in clinical use.…”
Section: Carcinogenicity Studies In Rodentsmentioning
confidence: 99%
“…Interpretation of the insulin glargine studies was further complicated by a very high early mortality rate, which was probably due to hypoglycaemia at the higher insulin doses. This led the US Food and Drug Administration (FDA) to comment that 'the findings in female mice were not conclusive due to excessive mortality in all dose groups' [40], a caution which, curiously, finds no echo in the published report of the study [39]. Mammary tumours did indeed develop in 10-20% of the female rats, but were no more common in rats treated with insulin glargine than in those treated with neutral protamine Hagedorn (NPH) insulin or control solutions.…”
Section: Carcinogenicity Studies In Rodentsmentioning
confidence: 99%
“…Accordingly, insulin analogues are divided into two subgroups known as long-acting and short-acting analogues. Although the clinical pharmacology of the insulin analogues in terms of glycemic control have been amply published [3], the long-term effects of most of these analogues have not yet been systematically evaluated [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the concern for glargine interfering with fetal development [62]. However, studies in rats and mice failed to show an increase in tumor formation with prolonged glargine exposure [49,63]. Furthermore, Pollex et al [62] carried out an in vitro transplacental transfer study and demonstrated undetectable transfer of glargine at therapeutic concentrations of 150 pmol/L [64].…”
Section: Glarginementioning
confidence: 99%